Pengaruh Program GRSSIA (Gerakan Rumah Sakit Sayang Ibu dan Anak) Terhadap Kejadian Stunting Balita di RSUD Sayang Cianjur Tahun 2023 - Ima Agustina; Susaldi Susaldi; Aida Diana Astarie (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Stunting is a disorder of child growth and development due to chronic malnutrition and recurrent infections, and inadequate psychosocial stimulation which is characterized by the length below based on age the standard (-2SD/Stunted). Stunting occurs with age in the first 1000 days of life (fetus up to 24 months) and children up to 60 month. The GRSSIA (movement of hospital in safe motherhood and childhood) is an innovation programme held by the public hospital in the cianjur area in an effort to reduce maternal mortality, baby and child expecially accelerate the process of preventing and reducing stunting in cianjur district. The purpose of this study was to determine the effect of the GRSSIA (gerakan rumah sakit sayang ibu dan anak /movement in hospital of safe motherhood and childhood) programme on the stunting incidents at the regional public hospital of sayang cianjur in 2023. This type of research is quantitative with a quasy experimental one group pretest-posttest design approach. The sampling technique used is non-random sampling type of total sampling are 55 childrens meet the inclusion and exclusion criteria. The instruments used were the observation sheet, microtoise, and reference of children antropometri. Statistical test using the paired t test. The result showed a p-value of 0.000 < 0.05 which means that there is influence of GRSSIA (Gerakan Rumah Sakit Sayang Ibu dan Anak/Movement of hospital in safe motherhood and childhood) programme on the stunting incidents at the regional general hospital of sayang cianjur in 2023.